Dysplastic L5-S1 Spondyloptosis in a 3-Year-Old Child: A Case Report and Review of the Literature - Vikas Tandon; Rahul Kaul; Harvinder Singh Chhabra; Ankur Nanda (Case Reports in Orthopedics)
A three-year-old girl presented with primary complaint of severe low back pain with radiation to both lower limbs below the knees since 2 months following history of fall and marked restriction of her daily routine activities. After clinicoradiological evaluation she was diagnosed of having dysplastic L5-S1 spondyloptosis. A staged procedure was planned after thorough discussion with her parents. During initial stage she underwent posterior decompression along L5-S1 segment including exposure of bilateral L5 and S1 nerve roots followed by instrumented reduction (L3-S2 5.5 mm pedicle screws) utilizing a rotational-translational technique. No interbody fusion was done at L5-S1 level and inner nuts of bilateral L3, L4, and S2 screws were intentionally kept loose. Subsequently after about symptom-free three-year follow up, she presented with recurrence of symptoms and underwent revision surgery as per initial plan discussed with her parents. Removals of posterior implants were done followed by stabilization with larger diameter pedicle screws (6.5 mm) at L5 and S1 level. During the same stage through anterior transperitoneal approach L5-S1 interbody fusion was done. At one-year follow-up after second-stage definitive surgery, patient remains symptom-free and fully active without any radiological evidence of reduction loss or implant failure.